Symptomatic spinal cord compression: an uncommon symptom in pseudohypoparathyroidism. Issue 1 (4th March 2021) - Tan, Xiaoping; Guo, Yang; Liu, Yan; Liu, Cong; Pei, Lina
Abstract: We describe symptomatic spinal cord compression associated with pseudohypoparathyroidism (PHP) in a young female patient and reviewed similar cases previously reported in the literature. The characteristics of these cases were analyzed from etiology, clinical subtypes, symptoms, treatment, and prognosis. Neurological examination revealed functional upper extremities with bilateral lower extremity paraplegia. Laboratory tests showed hypocalcemia, hyperphosphatemia, and elevated parathyroid hormone; high‐throughput sequencing showed a heterozygous GNAS mutation in exon 12, specifically c.1006C > T (p.R336W). Imaging findings showed multilevel spinal stenosis with significant spinal cord compression at the T2–T3 level. Seventeen cases with similar characteristics were reviewed. We found that the primary clinical manifestation of these patients was bilateral lower extremity spastic paraplegia. Multilevel spinal cord compression was commonly observed, especially at the lower cervical and upper thoracic spinal cord. Most of the patients had poor surgical treatment outcome and prognosis. Clinicians should be aware of paraplegia due to spinal cord compression as a rare neurological complication in patients with PHP. Early diagnosis and treatment of PHP is one basis for preventing severe spinal cord–related complications. Abstract : We describe symptomatic spinal cord compression associated with pseudohypoparathyroidism (PHP) in a young female patient and review similar cases previously reported in the literature. Multilevel spinal cord compression was commonly observed, especially at the lower cervical and upper thoracic spinal cord. Most of these patients had poor surgical treatment outcome and prognosis. Early diagnosis and treatment of PHP is one basis for preventing severe spinal cord–related complications.